2015
DOI: 10.1037/a0038236
|View full text |Cite
|
Sign up to set email alerts
|

Compassionate love buffers stress-reactive mothers from fight-or-flight parenting.

Abstract: The links among mothers’ compassionate love for their child, autonomic nervous system activity, and parenting behavior during less and more challenging mother–child interactions were examined. Mothers expressed and reported less negative affect when they exhibited autonomic patterns of increased parasympathetic dominance (high parasympathetic and low sympathetic activation) or autonomic coactivation (high parasympathetic and high sympathetic activation) during the less challenging interaction and autonomic coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 33 publications
(54 reference statements)
3
61
3
Order By: Relevance
“…That mothers’ SCL augmentation and RSA withdrawal, as main effects and in interaction with one another, while parenting were not significantly directly associated with maternal sensitivity is inconsistent with prior research in other samples (Lorber & O’Leary, 2005; Miller et al, 2015; Mills-Koonce et al, 2009; Moore et al, 2009; Sturge-Apple et al, 2011). However, in this sample, we have found indirect links between physiology and sensitivity via mothers’ self-reported emotions and cognitions while parenting (Leerkes et al, 2015; in press).…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…That mothers’ SCL augmentation and RSA withdrawal, as main effects and in interaction with one another, while parenting were not significantly directly associated with maternal sensitivity is inconsistent with prior research in other samples (Lorber & O’Leary, 2005; Miller et al, 2015; Mills-Koonce et al, 2009; Moore et al, 2009; Sturge-Apple et al, 2011). However, in this sample, we have found indirect links between physiology and sensitivity via mothers’ self-reported emotions and cognitions while parenting (Leerkes et al, 2015; in press).…”
Section: Discussioncontrasting
confidence: 79%
“…In the second study, Miller, Kahle, Lopez, and Hastings (2015), used an approach to assess patterns of SNS/PNS activation proposed by Berntson, Norman, Hawkley and Cacioppo’s (2008). They standardized separate indicators of mothers’ SNS activation (cardiac pre-ejection period) and PNS activation (RSA) during challenging joint problem solving tasks with their children, and then calculated their sum and their difference.…”
Section: Indirect Effects On Infant Outcomes Via Maternal Sensitivitymentioning
confidence: 99%
“…This is in keeping with studies that documented a functional link between empathic concern and the motivation to help others and care for their wellbeing (Batson, 2012; Gleichgerrcht & Young, 2013). Further, a large body of research has demonstrated that empathic concern is associated with prosocial behavior in both children (Davidov et al, 2013; Williams et al, 2014) and adults (Batson, 2009; Miller, Kahle, Lopez, & Hastings, 2014). This finding is also in line with clinical diagnostic criteria for psychopathy in both forensic and community samples, as well as theories of psychopathy, that emphasize the lack of concern and callous disregard for others’ feelings as a hallmark of the disorder (Hare, 1999; Kiehl, 2014; Malterer et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The examiner then attached an identical cardiac monitor to the child, which was worn for the rest of the visit. Mothers remained with their children for the first hour of the visit, as they completed several tasks together (see Miller, Kahle, Lopez, & Hastings, 2015), then the mother and child were separated and the child completed several tasks with the experimenter, beginning with Impossibly Perfect Circles, an anger induction task adapted from the Laboratory Temperament Assessment Battery (Goldsmith & Rothbart, 1996).…”
Section: Participants and Proceduresmentioning
confidence: 99%